Finite element procedures - Claude-Jurgen Bathe (Prentice-Hall, 1996)
The book considers three important items. First, it discusses the important point that is any analysis selected by a mathematical model of a physical problem, and then it solve that model. The finite element method is employed to solve very complex mathematical models, but it is important to realize that a finite element solution can never give more information than that contained in the mathematical model. Then, the book discusses the importance of finite element analysis in the complete process of computer-aided design (CAD). The last, the book addresses the question of how to study finite element methods